First-Line Treatment for Advanced Pancreatic Cancer - Kothari, Nishi; Saif, Muhammad Wasif; Kim, Richard (JOP. Journal of the Pancreas, 2013)
Metastatic pancreatic cancer is a rapidly fatal disease with few therapeutic options. The authors summarize four abstracts (#148, #233, #158, #291) presented at the 2013 ASCO Gastrointestinal Cancers Symposium which were focused on novel agents for metastatic pancreatic cancer. Image: Logo (H. Lee Moffitt Cancer Center. Tampa, FL, USA).